Risk analysis on hazard in high-rise construction project in Pulau Pinang / Muhammad Faisyafiq Abdul Fatah and Asmalia Che Ahmad - Abdul Fatah, Muhammad Faisyafiq; Che Ahmad, Asmalia (2020)
Falls from height, being hit by moving construction vehicles, hit by moving object, fall into bore hole and injuries from manual handling operations are some of hazards for high rise construction project. A study on the occupational safety for high rise construction projects was conducted which to identify the task of construction works in relation of safety, to determine the hazard that involves with high rise construction works, and to measure the level of risk for high-rise construction. So, the aim for this final project is to explore hazard and risk for high rise construction project. Around 50 sets of online questionnaires survey have been distributed through online because of pandemic covid-19. From that number, a total of 31 responds were collected. The process of data collection was done through the quantitative data collection method which is close ended questionnaire. The data were then analyzed by using excel to compose average index descriptive analysis where needed to calculate the risk assessment. The result concluded that the high risk accident is mostly occurred in falls from height and falling object. Based on the feedback from respondents, responsibility of the employer is more important which the employer must provide safety training to all workers during tool box talk. Otherwise, employer must also supply the information on hazard and risk for high rise construction project. Nevertheless, workers must comply the construction activity for high rise according to instruction and standard operation procedure.